Emotional stress and coping mechanisms: experience of poor rural women from Matlab, Bangladesh - Ahmed, Syed Masud; Chowdhury, Mushtaque; Bhuiya, Abbas (BRAC Research and Evaluation Division (RED), 2020)
Poverty is increasingly being recognised as a risk factor_ for both the development and the maintenance of common mental problems such as anxiety and depression. T-his study explored the experience of emotional stress by poor Bangladeshi rural women involved in credit-based income generating activities, using data from BRAC-ICDDR, Joint Research Project at Matlab. Out of 3,831 ever married women between 15 to 55 years, 39% from BRAC households reported suffering emotional stress in last four months, compared to 44% and 29"/o among poor and non-poor non-member households respectively. The single major reason was related to poverty (around 40%). The multivariate analysis identified currently married status, good health, generating family income and owning land by household as important predictors for better mental health. Disputes with neighbours, need to sell household assets. having poor health and having children, contributed to greater emotional stress. Around 44% of the women manifested symptoms of depression while coping with such situations. Also, change in women's economic roles within household was found to be initially met with resistance/ resentment, and in extreme cases, with physical violence. Thus, stresses resulting from newly adopted non-traditional role by women might act as risk factors for initiating mental health problems.